Effect of Different Fertilizations on the Plant-Available Nitrogen in Soil Profile (0–100 cm): A Study on Chinese Cabbage - Ahmed, Rasheed; Mao, Lili; Li, Yuzhong; Ding, Junjun; Lin, Wei; Ahmed, Shakeel; Abbas, Asad; Ahmed, Waseem (Frontiers in Plant Science, 2022)
The aim of this study is to analyze the variations in the plant-available nitrogen (PAN) concentrations in the soil profile. Different fertilizers were applied for Chinese cabbage plantation (CCP) in the experiment fields of Shunyi region. The treatments were used for the comparative analysis namely as: (i) no fertilizer and plantation (NVP), (ii) no fertilizer with CCP (CTP) and (iii) fertilization as urea (URP), (iv) potassium nitrate (KNP) and chicken manure (CMP) with CCP. It was concluded that yield was significantly high in URP, CMP and KNP as compared to CTP. In URP, maximum PAN in soil layers 0-60cm was recorded during crop production and in 60-100cm after harvesting as compared to other treatments. Significant variations were observed in soil pH and EC for the soil profile (0-100 cm) from the initial values with respect to time and treatments. CMP showed maximum ammonium in the upper layers 0-60 cm throughout the season, whereas minimum PAN was observed in NVP but increased in lower layers 60-100 cm. In general, all fertilizers raised the PAN below the soil 60-100cm which indicates their potential for the nitrate leaching (NL).